The demotic process in Astro star quest contestants from 2006-2016 / Ang Shiao Chien - Ang, Shiao Chien (2018)
In the past decades, scholars in the field of popular music study into demotic turn or celebrification. However, there is a lack of study in Malaysia, even in Asian countries. Many scholars also argued that the cultural and social needs in the perspective of building up the images of celebrity. Therefore, this research took on a case study in examining the demotic turn in Astro Star Quest and its impact upon celebrification of local Chinese popular artist in Malaysia. Astro Star Quest (ASQ) has long impacted the local C-pop industry nurturing popular musical talents, with notable example including Nicholas Teo, Gary Chaw, Vincent Chong, Anthony Tan and many more. In addition, this study also investigates as to whether there is a modelling pattern in ASQ in developing and marketing Malaysian Chinese pop artists.This qualitative research took on a naturalistic inquiry approach and was conducted in three ways towards (a) Participant observation, (b) observation and (c) individual in-depth interview. Outcomes reveal the music and image making process and changes in ASQ from year 2006 to 2016. Data from the study including the career prospect of the artists were analyzed and discussed based on Frith’s and Auslander’s theory of star personality, song personality and real personality. As a conclusion, the study shows how ASQ delivered a demotic turn in shaping the artist’s image and singing style, and not only that, it is important in its role in developing the Malaysian C-pop industry.